Spectrum, Etiology and Clinical Features of Intracranial Hypertension Presenting in NeuroOphthalmology Clinic At AFIO Rawalpindi - Ijaz, Umar; Saeed, Kamran; Sarwar, Imran; Nazir, Noman; Rathore, Hassan Sajjad; Shahid, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the clinical spectrum and various etiological factors of idiopathic intracranial hypertension in Pakistani patients.Study Design: Cross-sectional study.Place and Duration: Neuro-Ophthalmology Clinic, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jan 2017 to Jul 2018.Methodology: A total of 64 individuals with intracranial hypertension (IH) were screened. On the basis of inclusion criteria 32 patients were selected for the study. The demographics, clinical features and etiologies were recorded for each patient.Results: High frequency was noted among females, affecting 26 (84.37%) as compared to males who were 6 (18.75%) in number. Half of the patients had body weight lying in range of overweight, 16 (50%), however, only 5 (15.6%) patients fell into the category of obesity. Among clinical features, headache was the most prominent symptom seen in 17 (53.12%) patients and severe disc swelling seen in 19 (59.3%) was the most common sign. Most prevalent systematic association was anemia, 11 (34.3%), and the most prominent etiology was idiopathic intracranial hypertension, being 26 (81.25%).Conclusion: There was high frequency of intracranial hypertension in the females with obesity, pregnancy and in the age group of 20-30 years.